Delegated Portfolio Management, Benchmarking, and the Effects on Financial Markets - Igan, Deniz (IMF Working Papers; Working Paper ;, 2015)
We analyze the implications of linking the compensation of fund managers to the return of their portfolio relative to that of a benchmark-a common solution to the agency problem in delegated portfolio management. In the presence of such relativeperformance- based objectives, investors have reduced expected utility but markets are typically more informative and deeper. Furthermore, in a multiple asset/market framework we show that (i) relative performance concerns lead to an increase in the correlation between markets (financial contagion); (ii) benchmark inclusion increases price volatility; (iii) home bias emerges as a rational outcome. When information is costly, information acquisition is hindered and this attenuates the effects on informativeness and depth of the market.